2009
DOI: 10.1128/ec.00088-09
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for VeA and LaeA in Development and Pathogenesis ofAspergillus flavus

Abstract: Aspergillus flavus, a mycotoxigenic filamentous fungus, colonizes several important agricultural crops, such as maize and peanuts. Two proteins, VeA and LaeA, known to form a nuclear complex in Aspergillus nidulans have been found to positively regulate developmental processes in several Aspergillus species. Here, an examination of near-isogenic A. flavus mutants differing in copy number of veA and laeA alleles (0, 1, or at least 2 each) revealed critical roles for VeA and LaeA in A. flavus development and see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 41 publications
(66 reference statements)
5
144
2
Order By: Relevance
“…Two critical members of the Velvet complex are LaeA, a global regulator of SM (1,5,8,29), and VeA, or velvet, involved in the regulation of diverse cellular processes, including asexual and sexual development (11,28) as well as secondary metabolism (26,31). Deletion of either gene leads to a loss or decrease of SM production, and overexpression leads to enhanced production (1,5,8,20,26,43). Currently, the manner in which Velvet controls SM production is unknown, although LaeA activity is increasingly linked to chromatin modifications (37,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two critical members of the Velvet complex are LaeA, a global regulator of SM (1,5,8,29), and VeA, or velvet, involved in the regulation of diverse cellular processes, including asexual and sexual development (11,28) as well as secondary metabolism (26,31). Deletion of either gene leads to a loss or decrease of SM production, and overexpression leads to enhanced production (1,5,8,20,26,43). Currently, the manner in which Velvet controls SM production is unknown, although LaeA activity is increasingly linked to chromatin modifications (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…LaeA, a putative methyltransferase, was first identified in Aspergillus nidulans (5), A. fumigatus (6), and, subsequently, A. flavus (25). Overexpression (OE) of laeA increases the production of multiple metabolites in the aspergilli, whereas deletion of laeA silences expression of SM genes (1,5,8,20). LaeA is thus used as a genomic mining tool, providing a novel method for identifying new SM through microarray and chemical analyses (8,20,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In N. crassa, A. nidulans and Penicillium chrysogenum, deletion of veA orthologues leads to an increase in light-independent conidial formation, whereas deletion in Aspergillus parasiticus and Aspergillus fumigatus results in a general decrease in conidiation, which is dependent on the nutritional composition of the medium (Bayram et al, 2008;Calvo et al, 2004;Hoff et al, 2010, Krappmann et al, 2005Mooney & Yager, 1990). A reduction in conidiation has also been observed in Aspergillus flavus and Fusarium fujikuroi veA orthologue deletion mutants (Amaike & Keller, 2009;Wiemann et al, 2010).…”
Section: Global Regulation By the Velvet Proteinmentioning
confidence: 95%
“…In A. flavus it has been shown that laeA is a negative regulator of veA transcription (Kale et al, 2008). In addition, increased expression of veA (in a strain with multiple veA copies) results in decreased laeA expression (Amaike and Keller, 2009), suggesting a mutual negative transcriptional regulatory feedback control. In addition to transcriptional regulation between veA and laeA, recent studies also suggest posttranslational regulation (Bayram et al, 2010); a new form of the VeA protein with higher molecular weight has been detected in laeA strains, indicating that in the wild type, laeA prevents a modification of the VeA protein (Bayram et al, 2010).…”
Section: Global Regulationmentioning
confidence: 99%